AB0173 Active anti-VEGF immunization ameliorates collagen induced arthritis. (23rd January 2014) - Semerano, L.; Assier, E.; Duvallet, E.; Denys, A.; Adam, E.; Bernier, E.; Grouard-Vogel, G.; Boissier, M.-C.
Abstract : Background: Synovial neoangiogenesis is a key process in rheumatoid arthritis, contributing to pannus development and maintenance 1 . Anti-angiogenesis treatments targeting the VEGF/VEGF-R system ameliorate arthritis in several animal models 1, 2 . Here we report the results of active immunization against VEGF on mice collagen induced arthritis (CIA). Mice were immunized with the VEGF kinoid, a construct of murine VEGF and a carrier protein, the keyhole limpet hemocyanine (KLH), in order to induce a polyclonal anti-VEGF immune response and reduce synovial angiogenesis. Objectives: To determine: 1) the anti-VEGF immune response elicited by VEGF-K 2) the effect of VEGF-K on mice CIA. Methods: Forty DBA/1 male mice received 4 intramuscular injections of one of the following: VEGF-K (30-30-5-5μg; 20 mice), KLH (15-15-2.5-2.5μg; 10mice), and PBS (10 mice) as an emulsion with ISA51vg. Three injections were performed before, one after collagen administration. Arthritides were induced by two subcutaneous injections of bovine type II collagen, the first at day 0 in complete Freund adjuvant, the second at day 21 in incomplete Freund adjuvant. All the animals were monitored for clinical scores of arthritis and were sacrificed at day 61. Right forepaws and hind paws were kept for histological analysis. Anti-VEGF antibody (Ab) titers were determined by ELISA. Results: All VEGF-K treated mice produced anti-VEGF Ab. The VEGF group had lower mean clinical scores of arthritis vs. PBS and KLH groups and significantly lower scores of synovial inflammation (p<0.01) and destruction (p<0.01). In individual mice, moderate correlation between the area under the curve (AUC) of clinical scores and synovial inflammation (r=0.59 p<0.001) and destruction (r=0.54; p<0.0001) was found. Conclusions: Angiogenesis targeting with active anti-VEGF immunization in CIA results in anti-VEGF Ab production and reduction of synovial inflammation and destruction. References: Blood vessels, a potential therapeutic target in rheumatoid arthritis? Semerano L, Clavel G, Assier E, Denys A, Boissier MC. Joint Bone Spine. 2011 Mar;78(2):118-23. Peptides targeting inflamed synovial vasculature attenuate autoimmune arthritis. Yang YH, Rajaiah R, Ruoslahti E, Moudgil KD. Proc Natl Acad Sci U S A. 2011 Aug 2;108(31):12857-62. Disclosure of Interest: L. Semerano: None Declared, E. Assier: None Declared, E. Duvallet: None Declared, A. Denys: None Declared, E. Adam Employee of: Neovacs S.A., E. Bernier Employee of: Neovacs S.A., G. Grouard-Vogel Employee of: Neovacs S.A., M.-C. Boissier Grant/Research support from: Neovacs S.A., Consultant for: Neovacs S.A.